2015
DOI: 10.3892/mmr.2015.3264
|View full text |Cite
|
Sign up to set email alerts
|

Neuronic autophagy contributes to p-connexin 43 degradation in hippocampal astrocytes following traumatic brain injury in rats

Abstract: Connexins, gap junction proteins, have short half‑lives of only a few hours; therefore, degradation of these proteins can rapidly modulate their function. Autophagy is a type of degradation pathway that has been implicated in several diseases and was reported to be induced following traumatic brain injury (TBI). The aim of the present study was to investigate the involvement of neuronic autophagy in proteolysis of phosphorylated connexin 43 (p‑Cx43) in hippocampal astrocytes following TBI in rats. Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Next, the GFP-LC3 transfected N2a cells were incubated with M 3 -Cy5&Aβ 42 (20 μg·mL −1 /20 μM) for 4 h, followed by CLSM observation. Generally, LC3-II was recruited to the autophagosome membrane and thereby formed a green dot of GFP-LC3 when autophagy was activated 36 , 37 . As expected, the CLSM images revealed that most of the M 3 -Cy5 (red signal) colocalized with autophagosomes (GFP-LC3, green signal) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the GFP-LC3 transfected N2a cells were incubated with M 3 -Cy5&Aβ 42 (20 μg·mL −1 /20 μM) for 4 h, followed by CLSM observation. Generally, LC3-II was recruited to the autophagosome membrane and thereby formed a green dot of GFP-LC3 when autophagy was activated 36 , 37 . As expected, the CLSM images revealed that most of the M 3 -Cy5 (red signal) colocalized with autophagosomes (GFP-LC3, green signal) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…57 Following traumatic brain injury (TBI), autophagy inhibition caused increased levels of phosphorylated connexin 43 (pCx43) in hippocampal astrocytes, indicating autophagy based degradation of GJs. 58 A single or several AGJs can be engulfed simultaneously within an individual autophagosome. 54 Furthermore, plasma-membrane bound connexin proteins have been shown to be involved in early biogenesis of autophagosome.…”
Section: Autophagy Regulation Of Gap Junctionmentioning
confidence: 99%
“…Autophagy is involved in the pathological and physiological process of numerous diseases. However, no consensus has been reached on the effect of autophagy on organ function (16). A previous study has indicated that autophagy may lead to autophagic cell death or apoptosis, thus aggravating organ dysfunction (17).…”
Section: Discussionmentioning
confidence: 99%